POPULATION STRUCTURE OF DONAX STRIATUS (BIVALVIA, DONACIDAE) IN LAS BALSAS BEACH, GIBARA, CUBA - Ocaña-Borrego, Frank A.; Fernández, Alejandro; Silva, Alexis; González, Pedro A.; García, Yamilet (Revista Ciencias Marinas y Costeras, 2010)
Donax striatus Linné 1767 is one of the two beach clam species that inhabits in the Caribbean. Few investigations have focused on describing aspects related with the population structure of this species. A population of D. striatus was surveyed from February 2008 to January 2009 in Las Balsas beach, Gibara, Cuba. The population showed seasonal fluctuations of the density presenting the higher values on May and October 2008 and January 2009. There were peaks of recruitment: April-May, August 2008 and January 2009. A stratified distribution by size classes was observed: recruits were found in the higher strata of the beach while adults occur mainly in the lowest strata. The higher abundance was found in the middle strata. There was no correlation between monthly changes in density and temperatures, nor with the rainfall however, changes in the normal wave’s regimen and mid sea level rise seems to have some influence over the behaviour of this species abundance. A hypothesis that combines morphodynamics parameters to explain the across shore distribution of the components of the population, is proposed.